Analisis of Indications of Financial Statement Fraud: A Fraud Hexagon Approach - Astuti Anggraini; Einde Evana; Tri Joko Prasetyo (PT. Altaf Publishing Corp, 2025)
Financial statement fraud remains prevalent in Indonesia, particularly within the financial sector. This study aims to evaluate the influence of the six elements of the Fraud Hexagon theory on the occurrence of fraudulent financial reporting among companies in the financial industry. These six elements are operationalized through the following proxy variables: stimulus (financial stability), opportunity (ineffective monitoring), rationalization (auditor change), capability (director change), ego (arrogance), and collusion (whistleblowing system). The study population comprises all companies listed on the Indonesia Stock Exchange that were involved in financial statement fraud between 2019 and 2023. Using a purposive sampling method, the final sample consisted of 100 data points from 20 companies. Data analysis involved logistic regression, model fit testing, and both multivariate and univariate hypothesis testing. The results indicate that the variables opportunity, rationalization, and collusion significantly influence the likelihood of financial statement fraud, while stimulus, capability, and ego do not exhibit a statistically significant effect.